Daily life after healing of a venous leg ulcer: A lifeworld phenomenological study. Issue 1 (31st December 2022) - Rosenburg, Marcus; Fagerström, Cecilia; Tuvesson, Hanna; Lindqvist, Gunilla
ABSTRACT: Purpose: Venous leg ulcer is a recognized condition, affecting people globally. Ulcers mainly affect the elderly and recurrences are not uncommon. There is knowledge about life with venous leg ulcers, but the situation after healing is unexplored. This paper explores and describes meanings of experiences of daily life after healing of a hard-to-heal venous leg ulcer. Methods: Lived experiences of 15 individuals with healed hard-to-heal venous leg ulcers generated data for this study. Interviews were recorded for analysis using a reflective lifeworld research approach. An essence emerged, further described by its constituents. Results: Memories of a difficult time with leg ulcer were ever present, in a way becoming part of the self. A striving for control in daily life entailed a struggle to do what was best for the own body. After healing, a new normal emerged in daily life, a reality that encompassed the risk for a new ulcer. The body had changed physically, with marks alongside those from ageing, in a life that still went on. Conclusions: For those who had healed from a venous leg ulcer, life had changed. Even if they referred to life as normal, it was not the same normal as before.